Prevalence and severity of academic burnout in college students during the COVID-19 pandemic - Rosa Seperak-Viera; Manuel Fernández-Arata; Sergio Dominguez Lara (Interacciones, 2021)
Background: Academic burnout (AB) is an insidious process characterized by the feeling of emotional exhaustion due to the demands of academic life. Despite its impact on people's health, its prevalence has not yet been reported in Peru. The objective was to estimate the prevalence of AB, based on the emotional exhaustion experienced by university students, and the differences according to the student's year of study and sex. Method: Participants were 341 college students (76% women) from several institutions who were enrolled between the second and fourth year-of-studies. The Emotional Exhaustion Scale was used to measure students' AB. Results: The prevalence of AB was described by percentages and the comparison between groups was performed with effect size measures. The results reveal BA levels at a high level (31.4%) and risk (11.7%). On the other hand, women score higher than men in BA, but no differences were found according to the year of study. The association with anxiety and depression was moderate. Conclusions: The prevalence of academic burnout was significant, and it is associated with anxiety and depression.